PERSEMBAHAN TRADISIONAL MEK MULUNG DI MALAYSIA: PERUBAHAN STRUKTUR PERSEMBAHAN - Zahari, Zamzuriah; Yuszaidy Mohd Yusoff, Mohd (JURNAL MELAYU SEDUNIA, 2020)
This writing is about Mek Mulung’s performance who has to make a change. This is most essential so as to ensure Mek Mulung prevails in the modern entertainment world. Mek Mulung in its early stages is very related to a traditional element. Change of time, needs, technology, and outside demands has called for modification in Mek Mulung to stay in line with the current changes. Mek Mulung’s change refers to structure of performance so that it can carry on and remain relevant in today’s entertainment world. However, the change does not affect the Mek Mulung originality of presentation. Therefore, the objective of this study is to identify the change in structure of Mek Mulung. The process this research involves using a qualitative approach which uses field research and library. Field research, research had been undertaken at Kampung Wang Tepus, Kedah from year 2009 to the year 2019. This field research applies the observation method, participation and interviews. Likewise, observation and participation were done on individuals who are authoritative in Mek Mulung. This method was found to be suitable in collecting primary data. Meanwhile, the focused interview method was applied on individuals who were involved in Mek Mulung. Apart from that, the study also supported secondary library data. Retrieval study had found that some structure of performance had undergone modification. Survey results prove that change in structure has enabled enthusiasts to accept Mek Mulung and have it performed outside the district. Thus, this contribution was able to give new information to the case field of knowledge on traditional arts performance and give ideas to practitioners and younger generation of enthusiasts alike on Mek Mulung.